The impact of Brazil's tax-benefit system on inequality and poverty - Herwig Immervoll; Horacio Levy; José Ricardo Nogueira; Cathal O'Donoghue; Rozane Bezerra de Siqueira (Institute for the Study of Labor (IZA), 2006)
The Brazilian government raises taxes amounting to 35% of GDP and spends more than two thirds of this on social programmes. These shares are in pair with the OECD averages and well in excess of Latin America averages. However, while tax-benefit systems in most OECD countries reduce income disparities very significantly, the Brazilian government has been much less successful in alleviating inequality and poverty. Focussing on taxes and cash transfers, this paper investigates the impact of the government budget on the income distribution in Brazil, and evaluates its efficiency and effectiveness in reducing inequality and poverty. We present BRAHMS, a new tax-benefit microsimulation model for Brazil and illustrate its use by evaluating the impact of policy on economic inequality. It is argued that microsimulation provides a valuable analytical tool for policy makers in emerging and developing countries in particular.
Keywords: H22; H23; C81; 330; Brazil; inequality; poverty; redistribution; microsimulation